Role of the gut microbiota in the pathogenesis of endometriosis: a review - Guo, Cuishan; Zhang, Chiyuan (Frontiers in Microbiology, 2024)
Endometriosis is classically defined as a chronic inflammatory heterogeneous disorder occurring in any part of the body, characterized by estrogen-driven periodic bleeding, proliferation, and fibrosis of ectopic endometrial glands and stroma outside the uterus. Endometriosis can take overwhelmingly serious damage to the structure and function of multi-organ, even impair whole-body systems, resulting in severe dysmenorrhea, chronic pelvic pain, infertility, fatigue and depression in 5-10% women of reproductive age. Precisely because of a huge deficiency of cognition about underlying etiology and complex pathogenesis of the debilitating disease, early diagnosis and treatment modalities with relatively minor side effects become bottlenecks in endometriosis. Thus, endometriosis warrants deeper exploration and expanded investigation in pathogenesis. The gut microbiota plays a significant role in chronic diseases in humans by acting as an important participant and regulator in the metabolism and immunity of the body. Increasingly, studies have shown that the gut microbiota is closely related to inflammation, estrogen metabolism, and immunity resulting in the development and progression of endometriosis. In this review, we discuss the diverse mechanisms of endometriosis closely related to the gut microbiota in order to provide new approaches for deeper exploration and expanded investigation for endometriosis on prevention, early diagnosis and treatment.